Hatshepsut and the Apis Race: New Quartzite Relief Fragments from Dra’ Abu el-Naga - Aglan, Hassan (Études et Travaux, 2018)
The reconstruction of a scene sculpted on some quartzite stone fragments discovered recently at Dra’ Abu el-Naga and dating from the reign of Hatshepsut is the subject of this paper. The relief resembles the scenes known from the Red Chapel at Karnak and seems to be a part of the wdi sx.t ritual performed on the occasion of the Opet and/or Valley Festivals.